2010
DOI: 10.1007/s10461-010-9768-y
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Testing to Estimate Under-Reported Heavy Alcohol Consumption by Persons with HIV Initiating ART in Uganda

Abstract: Alcohol affects the transmission and treatment of HIV, yet may be under-reported in resource-limited settings. We compared self-reported alcohol consumption with levels of plasma carbohydrate-deficient transferrin (%CDT), a biomarker of heavy alcohol consumption, in persons initiating antiretroviral therapy in Uganda. Almost seven percent (6.7%) of persons reporting abstaining and 10% reporting consuming 1–40 drinks in the prior month tested positive for %CDT, and actual under-report may be higher due to low s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 11 publications
2
29
1
Order By: Relevance
“…Several recent quantitative and qualitative studies conducted in SSA have reported associations between alcohol consumption and ART adherence [39][40][41][42][43][44][45][46][47][48][49][50], while a few studies have found no association [51,52] or did not measure or report on alcohol consumption [53,54]. We echo the opinion that research focused on the effect of alcohol consumption on ART adherence specifically in SSA is needed [39], and note that careful consideration must be paid to methods of measuring alcohol consumption in this setting because under-report is likely [9]. We emphasize under-report because in a series of focus group meetings and key informant interviews in Kenya, Zambia, and Rwanda, discrepancies arose between reports by ART providers that alcohol problems in treatment are minimal, while patients reported that alcohol consumption on ART is common [8].…”
Section: Alcohol Consumption As a Risk Factor For Decreased Art Adhermentioning
confidence: 79%
See 1 more Smart Citation
“…Several recent quantitative and qualitative studies conducted in SSA have reported associations between alcohol consumption and ART adherence [39][40][41][42][43][44][45][46][47][48][49][50], while a few studies have found no association [51,52] or did not measure or report on alcohol consumption [53,54]. We echo the opinion that research focused on the effect of alcohol consumption on ART adherence specifically in SSA is needed [39], and note that careful consideration must be paid to methods of measuring alcohol consumption in this setting because under-report is likely [9]. We emphasize under-report because in a series of focus group meetings and key informant interviews in Kenya, Zambia, and Rwanda, discrepancies arose between reports by ART providers that alcohol problems in treatment are minimal, while patients reported that alcohol consumption on ART is common [8].…”
Section: Alcohol Consumption As a Risk Factor For Decreased Art Adhermentioning
confidence: 79%
“…1 The potential impact of alcohol consumption on HIV acquisition and HIV transmission. Alcohol consumption can directly impact HIV acquisition and transmission via sexual risk behavior, but may also increase the risk via co-infections that affect the immune system as well as decreased access to medical care and adherence to antiretroviral therapy (ART) reporting no alcohol consumption had in fact engaged in heavy alcohol consumption in the prior month [9]. Therefore, we suggest that due to the difficulty in measuring alcohol consumption and in gaining accurate self-report, estimates for alcohol consumption in the Africa region should be viewed with caution.…”
Section: Measurement Of Alcohol Consumption In Ssamentioning
confidence: 99%
“…Those with HIV were likely to have been instructed to cease drinking during their HIV clinic visits, and might fear that ART may be denied if they report drinking [49]. We have previously reported on the use of biomarkers to detect under-reported alcohol use in Uganda [50,51]; however, we were unable to collect biological markers to corroborate self-report in this study. Nonetheless, the correlates of baseline and follow-up drinking were consistent with previous literature; for example, men drinking and Moslems not drinking, which alleviates some of this concern.…”
Section: Discussionmentioning
confidence: 98%
“…Underreporting is common in the collection of survey data on alcohol consumption, as well as questions on sexual behaviors (Hahn et al, 2010;Minnis et al, 2009;Stockwell et al, 2004;Woolf-King & Maisto, 2011). Stigma or social desirability bias may cause respondents to under-report alcohol use in order to present themselves more favorably to the interviewer (Bowling, 2005;Greenfield & Kerr, 2008;Hahn et al, 2010;Hawkins et al, 2007). Underreporting may be especially pertinent to women's selfreported data on behavior related to sexual risk-taking and alcohol use.…”
Section: Discussionmentioning
confidence: 99%